Особливості формування системи контролінгу на промисловому підприємстві - Кубрак, Марина Олегівна (НТУ "ХПІ", 2017)
У статті проаналізовано й обґрунтовано необхідність застосування в практиці вітчизняних промислових підприємств системи контролінгу і визначено її характерні складові. Розглянуто три основні варіанти оформлення контролінгу в ієрархії підприємства, такі як контролінг без підрозділів, контролінг при створенні спеціального підрозділу і самоконтролінг.Запропоновано методичний інструментарій, який дозволить вчасно коригувати діяльність підприємства в процесі його виробничо-господарської діяльності.

The article analyzes and substantiates the necessity of using controlling systems in the practice of domestic industrial enterprises and determines its characteristic components.The role of controlling is shown, which in the crisis conditions acts as the unifying basis of the basic elements of an industrial enterprise and the management of its activities. The possibility of distributing all functions of controlling between existing divisions of the enterprise or the need to create new independent subdivisions. Three main variants of registration of controlling in the hierarchy of the enterprise are considered, such as controlling without divisions, controlling when creating a special unit and self-control. A methodological toolkit is proposed that will allow correcting the activity of the enterprise in time in the process of its production and economic activity.
Features of the formation of a controlling system in an industrial enterprise
Keywords: управління підприємством; контролер; рішення управлінські; management; controller; management solutions